Comparison of Fan-Traps and Gravitraps for Aedes Mosquito Surveillance in Taiwan - Pan, Chao-Ying; Cheng, Lie; Liu, Wei-Liang; Su, Matthew P.; Ho, Hui-Pin; Liao, Che-Hun; Chang, Jui-Hun; Yang, Yu-Chieh; Hsu, Cheng-Chun; Huang, Joh-Jong; Chen, Chun-Hong (Frontiers in Public Health, 2022)
A key component of integrated vector management strategies is the efficient implementation of mosquito traps for surveillance and control. Numerous trap types have been created with distinct designs and capture mechanisms, but identification of the most effective trap type is critical for effective implementation. For dengue vector surveillance, previous studies have demonstrated that active traps utilizing CO2 attractant are more effective than passive traps for capturing Aedes mosquitoes. However, maintaining CO2 supply in traps is so labor intensive as to be likely unfeasible in crowded residential areas, and it is unclear how much more effective active traps lacking attractants are than purely passive traps. In this study, we analyzed Aedes capture data collected in 2019 from six urban areas in Kaohsiung City to compare Aedes mosquito catch rates between (passive) gravitraps and (active) fan-traps. The average gravitrap index (GI) and fan-trap index (FI) values were 0.68 and 3.39 respectively at peak catch times from June to August 2019, with consistently higher FI values calculated in all areas studied. We compared trap indices to reported cases of dengue fever and correlated them with weekly fluctuations in temperature and rainfall. We found that FI trends aligned more closely with case numbers and rainfall than GI values, supporting the use of fan-traps for Aedes mosquito surveillance and control as part of broader vector management strategies. Furthermore, combining fan-trap catch data with rapid testing for dengue infections may improve the early identification and prevention of future disease outbreaks.